Nepal’s misinformation domain-comparing mainstream journalists and content creators - Anupam, Birat (Nepali Media: Issue of Ethics and Sustainability, 2025)
From the era of dot pen to the era of dot.com, Nepal's media landscape has traversed a long journey both in terms of medium and content. Misinformation is as long as Nepali media's journey. This article aims to pinpoint the increasing trends of Nepal's misinformation domain inundated by both legacy media journalists and content creators. With the evolution of new media, mainly the digital domains with various mighty social media platforms, Nepal has witnessed rapid rise of content creators having hundreds of thousands of followers which is almost the same as that of legacy media, if not more. Unchecked contents devoid of journalistic characters are giving rise to misinformation. The article uses publicly available data, relevant researches on misinformation front of Nepal in order to figure out the scenarios of misinformation. The article talks on initiatives taken by Press Council Nepal to douse the conflagration of misinformation. Finding says that misinformation generated by legacy media journalists is mainly owing to strong gate keeping and team failure. However, content creators' misinformation is mainly caused by their crowd-pleasing and emotion-driven sensational statements. The article concludes with recommendations for professional and moral encouragements involving fact checking, media literacy and digital literacy initiatives spearheaded by stakeholders like Federation of Nepali Journalists (FNJ), Press Council Neal, Department of Information, among others to build a scenario where journalists will be equipped with the trending technology and catchy contents as that of content creators and content creators will be skilled with journalistic code of conduct, gate-keeping and fact-checking.